1999
DOI: 10.1034/j.1600-051x.1999.260608.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal repair in dogs: histologic observations of guided tissue regeneration with a prostaglandin E1 analog/methacrylate composite

Abstract: This report describes observations of healing following guided tissue regeneration (GTR) including surgical implantation of the prostaglandin E1 analog misoprostol with calcium-layered methacrylate particles. Critical size, supra-alveolar periodontal defects were surgically created around the 3rd and 4th mandibular premolar teeth in 4 beagle dogs. Wound management included soaking with a 24 microg/ml misoprostol solution and implantation of the misoprostol/methacrylate composite. One jaw quadrant per animal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 19 publications
2
50
1
Order By: Relevance
“…The duration of the remodeling cycle in the mandibular alveolar bone is shorter than in the long bones [18]. In the long bones, the remodeling cycle is 20-30 days [7], whereas in the alveolar bone, it is 6 days plus a 5-day resting period [17].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The duration of the remodeling cycle in the mandibular alveolar bone is shorter than in the long bones [18]. In the long bones, the remodeling cycle is 20-30 days [7], whereas in the alveolar bone, it is 6 days plus a 5-day resting period [17].…”
Section: Discussionmentioning
confidence: 94%
“…Particularly as local delivery of prostaglandin E1 (PGE1) has been shown to enhance the formation of mandibular alveolar bone, reorganization of adjacent cells in the periodontal ligament and cementum formation [11,13,18]. The positive effect of PGE 2 on bone deposition has been reported with doses as low as 1 mg/kg per day delivered subcutaneously into different animal models over extended periods of time [1,6,9,20].…”
Section: Introductionmentioning
confidence: 99%
“…5,6,8,9 Collapse or compression of the barrier device into a periodontal defect or onto the root surface will necessarily compromise regeneration of alveolar bone and cementum following GTR procedures. [4][5][6][7][8][9] The space provided by the device at the time of surgery is lost and the device becomes a physical obstacle to bone and cementum regeneration. Thus, structurally reinforced GTR devices have been developed to safeguard wound stability and maintain necessary space provision.…”
Section: G Uided Tissue Regeneration (Gtr) Ismentioning
confidence: 99%
“…2,3 Studies have also shown that alveolar bone and cementum regeneration is critically dependent on space provision by the GTR device. [4][5][6][7][8][9] With limited space provision by the barrier membrane, alveolar bone will fill the space provided by the device. 4,9 In presence of a larger space, the alveolar bone adopts a physiologic form along the entire root surface, the remainder of the space being filled by fibrous connective tissue.…”
Section: G Uided Tissue Regeneration (Gtr) Ismentioning
confidence: 99%
See 1 more Smart Citation